Impact of the constructivist Bybee model on teaching method acquisition, retention, and deductive thinking - Bassim, Jamal Shukri (Universitas Tanjungpura, 2026)
Background Effective instructional models are essential for improving students' conceptual understanding, long-term knowledge retention, and higher-order thinking skills in teacher education. The constructivist Bybee model has gained attention for promoting active learning through inquiry-based instructional phases. Objectives This study examined the effects of the constructivist Bybee model on the acquisition and retention of teaching method concepts and the development of deductive thinking among third-year physical education students. Methods A quasi-experimental study with a pretest-posttest equivalent control group design was conducted during the 2022 to 2023 academic year at the University of Mosul. Third-year students from the College of Physical Education and Sports Sciences participated in the study. Participants were assigned to experimental and control groups after establishing equivalence and homogeneity across relevant demographic and academic variables. The experimental group received instruction using the Bybee model, whereas the control group followed conventional teaching methods. Data were analyzed by comparing pretest and posttest outcomes for concept acquisition, retention, and deductive thinking. Results Students instructed through the Bybee model demonstrated significantly greater gains in teaching method concept acquisition and retention than those receiving conventional instruction. The experimental group also achieved significantly higher deductive thinking scores, indicating that the constructivist learning process effectively supported cognitive development and strengthened logical reasoning. Conclusion The constructivist Bybee model is an effective instructional approach for enhancing conceptual learning, knowledge retention, and deductive thinking in physical education teacher education. Integrating this model into teaching methodology courses may improve both cognitive outcomes and instructional competence among future physical education teachers.